Concentration and Staining Duration Effects of Clitoria ternatea Extract on Wholemount Preparate Quality - Isna Putri Arifa; Eko Susetyarini; Nurul Mahmudati; Sri Wahyuni (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
Making intact preparations to observe the anatomical structure of plants and animals in biological practicum activities requires effective dyes. Synthetic dyes such as safranin are commonly used, but they are relatively expensive, carcinogenic, and less environmentally friendly. This study aimed to examine the effect of variations in concentration and duration of staining using telang flower extract (Clitoria ternatea) on the quality of the whole plant preparation Hydrocotyle umbellata. The study was conducted experimentally with a combination of concentration treatment (70%, 80%, and 90%) and duration of staining (15 and 30 minutes). The quality of the preparations was assessed using assessment parameters which included clarity of anatomical structure, colour contrast and colour distribution. The data obtained were analyzed to determine the best treatment combination, as well as compared with safranin-stained and no-staining control preparations. Results showed that increasing concentration and duration of staining had an effect on the quality of the preparation results. The combination of concentrations of 80% of the 15-minute duration of staining gave the best results with the identification of trichomes, strong color contrast and even color. Based on these results, telang flower extract has the potential to be used as a natural dye alternative to safranin which is safer, more economical and more environmentally friendly.